Developing an Islamic Education-Based Learning Management Model for Character Formation in Public Elementary Schools - Prasinta, Dian Jani; Patimah, Siti; Murtafiah, Nurul Hidayati (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aimed to develop and validate an Islamic education-based learning management model to strengthen students’ character formation in public elementary schools in Bandar Lampung, Indonesia. The study was motivated by the finding that character education in public schools had not yet been systematically integrated into instructional management and remained largely partial, incidental, and dependent on individual teacher initiative. Using a research and development design adapted from Borg and Gall and supported by a mixed-methods approach, the study was conducted in three public elementary schools: SDN 2 Sukajawa, SDN 2 Kupang Teba, and SDN 1 Sukarame Dua. Data were collected through observation, questionnaires, interviews, documentation, and validation instruments, and were analyzed qualitatively and quantitatively to examine the model’s validity, practicality, and effectiveness. The findings showed that the developed model was categorized as valid by experts and positively accepted by teachers and school principals as practical and feasible for implementation. The model also produced significant improvements in students’ spiritual and social attitudes across the participating schools, as confirmed by the paired-samples t-test results (t = -29.911, p < .001) and a moderate N-gain score of 0.39. These results indicate that systematic integration of Islamic values into instructional planning, classroom implementation, habituation, and evaluation can strengthen character formation in public elementary school contexts. This study contributes to the literature by offering an empirically tested and contextually grounded learning management model that extends Islamic character education from value transmission alone to a structured managerial framework applicable in mainstream public education.